Macrophages Promote Oxidative Metabolism To Drive Nitric Oxide Generation in Response to Trypanosoma cruzi - Koo, Sue-jie (Infect Immun, 2016)
Trypanosoma cruzi is the causative agent of chronic chagasic cardiomyopathy. Why macrophages (mφs), the early responders to infection, fail to achieve parasite clearance is not known. Mouse (RAW 264.7) and human (THP-1 and primary) mφs were infected for 3 h and 18 h with T. cruzi TcI isolates, SylvioX10/4 (SYL, virulent) and TCC (nonpathogenic), which represent mφ stimulation and infection states, respectively. Mφs incubated with lipopolysaccharide and gamma interferon (LPS/IFN-γ) and with interleukin-4 (IL-4) were used as controls. We monitored the cytokine profile (using enzyme-linked immunosorbent assay [ELISA]), reactive oxygen species (ROS; fluorescent probes), nitric oxide (·NO; Griess assay), and metabolic state using a custom-designed mitoxosome array and Seahorse XF24 Analyzer. LPS/IFN-γ treatment of mφs elicited a potent increase in production of tumor necrosis alpha (TNF-α) at 3 h and of ROS and ·NO by 18 h. Upon SYL infection, murine mφs elicited an inflammatory cytokine profile (TNF-α ≫ TGF-β + IL-10) and low levels of ·NO and ROS production. LPS/IFN-γ treatment resulted in the inhibition of oxidative metabolism at the gene expression and functional levels and a switch to the glycolytic pathway in mφs, while IL-4-treated mφs utilized oxidative metabolism to meet energy demands. SYL infection resulted in an intermediate functional metabolic state with increased mitoxosome gene expression and glycolysis, and IFN-γ addition shut down the oxidative metabolism in SYL-infected mφs. Further, TCC- and SYL-stimulated mφs exhibited similar levels of cell proliferation and production of TNF-α and ROS, while TCC-stimulated mφs exhibited up to 2-fold-higher levels of oxidative metabolism and ·NO production than SYL-infected mφs. Inhibiting ATP-coupled O(2) consumption suppressed the ·NO generation in SYL-infected mφs. Mitochondrial oxygen consumption constitutes a mechanism for stimulating ·NO production in mφs during T. cruzi infection. Enhancing the oxidative metabolism provides an opportunity for increased ·NO production and pathogen clearance by mφs to limit disease progression.